Applying usability guidelines for e-commerce website for Islamic products / Nor Hafizah Ali - Ali, Nor Hafizah (2015)
As far as Muslims' welfare is concerned, Islam accords a paramount importance to the trading sector as a major source of wealth and gale force wheel of the economy. From an analysis, the conduct of e-commerce found to be as new way of technology accepted by Islam to facilitate economic transactions. The e-commerce implementation also has increased the sales revenue for most of the companies. By 2008, e-commerce transactions have reached $5 trillion worldwide. The usability is found to be an important aspect to be applied in e-commerce, but from a study, nearly more than 50% of the investigated Islamic websites have low usability level. The result of usability can be proved by e-commerce websites normally increased sales by 100% or more (Joshi, 2012). Since usability is crucial for e-commerce site and a happy customer will most likely to return, making their experience as good as possible must be one of the main objectives of online stores. There are many types of ecommerce products such as clothing, banking, online ticketing and many more. For this research it mainly focus on the development of e-commerce website for Islamic Products (focus on Hajj and Umrah products) based on usability guidelines. Basically, this research has three main objectives that need to be achieved. The first and second objectives are to design and develop e-commerce for Islamic Products based on ecommerce usability guidelines. The third objective is to evaluate the e-commerce for Islamic Products. The methodologies that have been adapted throughout this research include observations, user studies (interview and capture requirements) and development using Extreme Programming (XP). It is hoped that the finding of this research could assist the retailers in managing their products efficiently and ease the buying process of the customers.